The Divine Undergirding Of Human Knowing: Plato and Critical Realism - Trainor, Brain T. (Philosophy & theology, 2010)
Plato held that the Agathon (Being itself in its font) is the source or ‘common cause’ both of being(s) and of our understanding, both of the world (cosmos) and of our intellectual grasp thereof, both of the world beyond us (objectivity) that yet includes us and of the world of our inner thoughts (subjectivity) that yet stretches out to embrace the entire universe. This divine presupposition, found ‘philosophically’ in Plato and ‘religiously’ in Augustine’s doctrine of divine illumination, is that God is the common cause of us and our world, for both are held within the same divine/cosmic embrace, by the same Spirit operating within us and beyond us. This leads us to a ‘hand-in-its-glove’ or ‘mind-in-its-world’ proportionate realism that avoids the epistemological defects of Kant’s transcendental realism and Bhaskar’s critical realism. Finally, we should regard knowing by acquaintance as paradigmatic, as the fundamental form of knowing in terms of which the other types are best approached and understood. There is, I suggest, an important sense in which ‘all knowing is knowing in the biblical sense.’